Estudo da síntese de nanopartículas metálicas de paládio para uso em catálise heterogênea - Junges, Alexander (2011)
Palladium nanoparticles dispersed on supports have been widely studied over the past years due to their properties for particular applications in sensors and catalysts. In the catalysis field these supported nanoparticles are widely used in various industrial processes of economic importance, with paritcula interest in processes of hydrogenation and dehydrogenation, allowing an increase in the value of compounds from oil-chemical industry. The objective was the experimental study of the synthesis conditions of metallic nanoparticles of palladium supported on silica. Catalysts were synthesized by traditional methods of impregnation, as well as methods using reducing agents and stabilizers for metal nanoparticles. In the synthesis, different conditions were used in the catalysts prepare, by varying the concentrations of metal precursor (palladium nitrate), reducing agent (gallic acid) and stabilizer (polyvinylpyrrolidone), enabling a better understanding of how these conditions affect the dispersion of the metal catalyst, since the size and nature of the interaction of a particle with a metal oxide support are critical in determining the catalytic activity and selectivity. It were obtained nanoparticles with sizes ranging from 3.28 to 16.92 nm, synthesized by different methods, the dispersion of the catalyst where it was used reducing agent and stabilizing agent were, in most cases, similar to those obtained by the traditional method of impregnation, probably due to the high temperatures used in calcination to remove the reducing and stabilizing agent. Finally, the result that became apparent is that the gallic acid itself acts as a reducing agent and protective agent of the nanoparticles, what can facilitate the steps of calcination, since it is not necessary the presence of a protective agent such as PVP polymer, whose thermal degradation is more difficult. On the other hand, in the synthesis of catalysts, the presence of PVP apparently has a little contribution in the dispersion of palladium nanoparticles. More efforts must be devoted to the controlled synthesis of nanoparticles of the metal palladium to be more versatile to promote or catalyze reactions or active components in the manufacture of nanoscale devices.